Revisiting Capitalism through Social Business Model - Bhandari, Krishna Raj; Baral, Kshitiz (Janapriya Journal of Interdisciplinary Studies, 2019)
Seeing the fall of the Berlin Wall and the collapse of the Soviet Union gave a false hope to the proponent of capitalism that it is the only hope for the future. However, this very belief is crumbling the western societies with the rise of the populism and nationalism. Amidst this confusion, this paper revisited the published literature on social business model suggested by Nobel Laureate prof. Muhammad Yunus and added a new dimension of entrepreneurial attention suggested by Ocasio (1997). Propositions are derived on how the entrepreneurial attention increases the sustainable performance of the social business.